DIGITAL INSTRUMENTS FOR ENSURING THE SECURITY OF ECONOMIC AGENTS: CURRENT REALITIES AND MAIN VECTORS OF DEVELOPMENT - VIVCHAR, OKSANA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
In modern conditions of turbulence of economic processes, the urgency of digitalization in the security system of economic agents is steadily increasing. The relevant topic is becoming especially relevant in the context of the COVID-19 pandemic, when the resources of business structures may change in the focus of applied aspects and focus more on projects to develop internal efficiency and provide a non-knowledge component. Based on research, it has been established that digital tools for strengthening the security of economic agencies create new risks and challenges, including threats to cybersecurity, facilitation of illegal economic activities and more. After all, digitalization is a factor that provides significant benefits for development in this direction. Economic growth and transformation are happening through the expansion and more convenient use of digital technologies. Thus, rapid changes in the development and competitiveness of economic agents towards the use of digital transformation are inevitable. Research suggests that digitalization is a catalyst for innovative development, technological change has led to opportunities such as flexibility, reactivity and individualization of products, but at the same time there are new challenges and threats such as rapid technological transformation, high level of complexity, changing customer preferences and legal requirements. The article examines the conceptual and categorical apparatus of «digitalization» and the algorithm of the process digitalization of economic agents in the context at security conditions. The practical tools of methods and algorithms (SADT, IDEF, UML, BPMN), which provide automation of workflow management using web-technologies are substantiated. As a result of scientific research the main vectors of ensuring the security economic agents in modern conditions of digitalization economic processes have been identified. On the basis of which key forms of realization digital processes on the state and possibilities of development strengthening safety at economic agents are characterized. The peculiarities of providing appropriate security components in the conditions of active processes of digitalization economic relations are investigated.